2017
DOI: 10.1002/ajmg.a.38260
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotic bone lesions in tuberous sclerosis complex: A genotype–phenotype study

Abstract: Tuberous sclerosis complex (TSC) is due to pathogenic variants in TSC1 or TSC2 genes resulting in hyperactivation of the mTOR pathway. Many organ systems can be affected, such as brain, skin, eye, heart, bone, kidney, or lung. Sclerotic bone lesions have been reported as frequent findings in TSC although they are not considered diagnostic criteria. The objective of this study is to characterize sclerotic bone lesions detected by chest CT in a large cohort of adult TSC patients and to correlate with genotype. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Pancreatic neuroendocrine tumors, while overall rare (9/219; 4.1% in one study [69]), remain the most common pancreatic neoplasia in individuals with TSC [69]. Many more manifestations have been reported, such as sclerotic bone lesions [97] and cerebellar lesions in individuals with a TSC2 mutation [98] (see Table 1). The full scope of manifestations is however out of the scope of this non-systematic clinical overview.…”
Section: Other Organ Manifestationsmentioning
confidence: 95%
“…Pancreatic neuroendocrine tumors, while overall rare (9/219; 4.1% in one study [69]), remain the most common pancreatic neoplasia in individuals with TSC [69]. Many more manifestations have been reported, such as sclerotic bone lesions [97] and cerebellar lesions in individuals with a TSC2 mutation [98] (see Table 1). The full scope of manifestations is however out of the scope of this non-systematic clinical overview.…”
Section: Other Organ Manifestationsmentioning
confidence: 95%
“…The first one concerns bone manifestations in this condition, consisting of sclerotic bone lesions, bone cysts, and fibrous dysplasia. Sclerotic bone lesions are usually multiple and can be present in up to 90% of adult patients (Avila et al, ; Boronat, Barber, & Thiele, ). Although they might not be specific for TSC, recent evidence from a case–control study evaluating CT scans of 49 adults with TSC suggests that sclerotic bone lesions are found more frequently in TSC patients than in the general population (Brakemeier et al, ).…”
Section: Clinical Manifestations Of Tsc In Adulthoodmentioning
confidence: 99%
“…A chest CT study in 107 adult TSC patients demonstrated a high prevalence of multiple SBLs (four or more) in 91% of cases, and 98% of patients showed at least one SBL (Avila et al, 2010). This was supported by another study showing sclerotic bone lesions in 82/92 (89%) TSC adult patients (Boronat et al, 2017). SBLs are preferentially located in the posterior elements of vertebrae, mainly pedicles and laminas (Figure 4a,b).…”
Section: Bone Lesionsmentioning
confidence: 77%
“…As SBLs usually do not produce symptoms, patients do not usually undergo biopsy, and genetic analysis of TSC1/TSC2 has not been performed yet in any of these lesions, so it is not known if they follow a second-hit model, as other lesions in TSC (Crino, Nathanson, & Henske, 2006). CT is the preferred diagnostic modality for assessing sclerotic bone lesions in TSC (Avila et al, 2010;Boronat, Barber, & Thiele, 2017;Brakemeier et al, 2018) although they may also be detected by MRI (Boronat, Barber, Pargaonkar, Chang, & Thiele, 2016;Stosic-Opincal et al, 2005).…”
Section: Bone Lesionsmentioning
confidence: 99%